The Long-Term Esthetic and Radiographic Outcome of Implants Placed in the Anterior Maxilla after Ridge Preservation, Combining Bovine Xenograft with Collagen Matrix - Leonidas Batas; Vithleem Xanthopoulou; Maria Gnigou; Triantafyllia Vagdouti; Ioannis Fragkioudakis; Ioannis Vouros (Dentistry Journal, 2024)
The objective of the study was to evaluate the long-term esthetic and radiographic results of implants placed in the anterior maxilla after ridge preservation, combining bovine xenograft with collagen matrix. Fifteen patients who required a single tooth extraction because of fracture, root resorption, or extended caries were included in the study. After extraction, all sites were grafted using Deproteinized Bovine Bone Mineral (DBBM) with collagen and covered by a resorbable collagen matrix (CM). Five months after socket grafting, implants were successfully installed. The implant diameter range was between 3.8 and 4.2 mm. All patients were monitored for over 7 years, both clinically and radiographically. Three independent observers evaluated the long-term esthetic outcome, employing the Pink Esthetic Score (PES) technique. Over a period exceeding seven years, a 100% survival rate was observed for all 15 implants, with minimal marginal bone loss. The mean PES was 11.40 (±1.44) at the first assessment and 11.38 (±1.63) at the second assessment. The difference was not statistically significant (p = 0.978), and the scores of PES measurements indicated excellent esthetic results even after seven years. Based on these preliminary results, it seems that placing collagen bovine bone in a fresh extraction socket, covered with a collagen matrix, can preserve the alveolar ridge and provide long-term stable esthetic results.